PATRIARCHY, CASTE AND CLASS: . - Dietrich, Gabriele (Journal of Dharma, 1998)
The situation of Dalits, women and workers in the unorganized sector has often been dealt with as if we were dealing with sectoral problems of marginalized sections in society, which needed some welfare measures of social uplift in order to be integrated into the mainstream of development, sharing in the benefits brought about by economic growth. Government policies have looked a t things from this angle, and often demands of movements representing these different sections have also raised issues which amount to social welfare measures.